2017
DOI: 10.1007/978-3-319-67922-8_4
|View full text |Cite
|
Sign up to set email alerts
|

All-Star or Benchwarmer? Relative Age, Cohort Size and Career Success in the NHL

Abstract: We analyze the performance outcomes of National Hockey League (NHL) players over 18 seasons (1990-1991 to 2007-2008) as a function of the demographic conditions into which they were born. We have three main findings. First, larger birth cohorts substantially affect careers. A player born into a large birth cohort can expect an earnings loss of roughly 18 percent over the course of an average career as compared to a small birth cohort counterpart. The loss in earnings is driven chiefly by supply-side factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Take for example a recent analysis by Bryson, Gomez and Zhang (2015), who consider the Relative Age, Cohort Size and Career Success in the NHL (National Hockey League). The authors analyse the performance outcomes of NHL players over 18 seasons between 1990-1991 and 2007-2008, with a focus on identifying the impact of demographic conditions into which a player was born.…”
Section: Identifying Where Generational Differences "Cut"mentioning
confidence: 99%
“…Take for example a recent analysis by Bryson, Gomez and Zhang (2015), who consider the Relative Age, Cohort Size and Career Success in the NHL (National Hockey League). The authors analyse the performance outcomes of NHL players over 18 seasons between 1990-1991 and 2007-2008, with a focus on identifying the impact of demographic conditions into which a player was born.…”
Section: Identifying Where Generational Differences "Cut"mentioning
confidence: 99%
“…Surprisingly, few studies have examined the RAE on player productivity in the National Hockey League (NHL) [ 7 , 8 ]. In these studies, there is evidence of a RAE reversal.…”
Section: Introductionmentioning
confidence: 99%
“…Fumarco (2015) used a sample of football players in the Italian Series A and …nd that players born relatively late in an age group receive lower gross wages than players born earlier. He mostly attributes these results to the players born in the December cohort (see also, Gibbs et al, 2012, andBryson et al, 2014). This suggests that the discrimination hurdle is indeed important to explaining the overachievement e¤ect and that general peer e¤ects alone are insu¢ cient to explain this phenomenon.…”
Section: The Populationmentioning
confidence: 99%
“…Stylized fact 1 documents a strong RAE for the Swedish U17 team. However, recently, Gibbs et al (2012), and Bryson et al (2014) have found that players born later in the year might perform better in the long run. Closely related to our study is that of Ashworth and Heyndels (2007), which provides a theoretical graphical analysis of the e¤ects of selection and peer in ‡uence 5 There is a small theoretical literature on tracking.…”
Section: Related Literaturementioning
confidence: 99%